1996
DOI: 10.1021/ja961505l
|View full text |Cite
|
Sign up to set email alerts
|

Salt Effects on Solvolysis Reactions of p-Nitrophenyl Alkanoates Catalyzed by 4-(Dialkylamino)pyridine- Functionalized Polymer in Buffered Water and Aqueous Methanol Solutions

Abstract: Specific salting-in effects that lead to striking substrate selectivity were observed for the hydrolysis of p-nitrophenyl alkanoates 2 (n = 2−16) catalyzed by 4-(dialkylamino)pyridine-functionalized polymer 1 in aqueous Tris buffer solution at pH 8.0 and 30 °C. Macromolecule 1 was found to exhibit clear substrate preference for 2 (n = 6) in 0.05 M aqueous Tris buffer solution, as contrasted with the corresponding reaction in 0.05 M aqueous phosphate or borate buffer solutions where the substrate selectivity is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…[~ -"1 We have reported that macromolecule 1 containing the 4-(dialkylamino)pyridine functionality and a bis(trimethy1ene)disiloxane backbone as a nucleophilic catalyst exhibits enzyme-like substrate selectivity for the solvolysis of 2 in aqueous and methanol/ water solutions.[". 13,14] To our knowledge, ion-induced substrate specificity changes have not been reported previously for catalytic ester solvolysis.…”
Section: Guang-jia Wang and Wilmer K Fife"mentioning
confidence: 99%
“…[~ -"1 We have reported that macromolecule 1 containing the 4-(dialkylamino)pyridine functionality and a bis(trimethy1ene)disiloxane backbone as a nucleophilic catalyst exhibits enzyme-like substrate selectivity for the solvolysis of 2 in aqueous and methanol/ water solutions.[". 13,14] To our knowledge, ion-induced substrate specificity changes have not been reported previously for catalytic ester solvolysis.…”
Section: Guang-jia Wang and Wilmer K Fife"mentioning
confidence: 99%
“…Macromolecule 1 is an amphiphilic polymer which contains distinct hydrophobic and hydrophilic regions, and it associates to form macromolecular aggregates by self-assembly in aqueous or methanol−water solution. The control of aggregate morphology changes of small-molecule and macromolecular amphiphiles from spheres to rods, and to vesicles by increasing the hydrophobic effects in water and water−organic solvent mixtures has already been well-established. For many years, the aggregate morphology changes of small-molecule amphiphiles from spherical micelles to micellar rods and vesicles have been known to be controlled by increases of their constituent concentrations in solution. The gradual changes of aggregate morphology of polystyrene- b -poly(2-vinylpyridine) copolymers from spheres to rods, and to vesicles have also been demonstrated with increasing copolymer concentration . Consistent with the notion that salt-induced hydrophobic effects control aggregate morphology of amphiphiles, the aggregate morphology of these copolymers in water−organic solvent mixtures can also be changed from spheres to rods, and to vesicles by addition of salting-out agents such as NaCl and CaCl 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The addition of salting-out agent NaCl leads to a change of substrate specificity from 2 ( n = 14) to 2 ( n = 12) in 1:1 (v/v) methanol−aqueous phosphate buffer solution , Moreover, we have reported an interesting example of electrostatic interactions that contribute to the catalytic activity and substrate specificity for the 1 -catalyzed solvolysis of 2 ( n = 2−18) in the presence of anionic surfactant sodium dodecyl sulfate (SDS), which provides significant insight into the mechanism of catalytic ester solvolysis. These results may be akin to the observations that many enzymes usually accelerate the hydrolytic reactions at hydrophobic binding sites by electrostatic stabilization of the transition state through interactions with nearby amino acid constituents. , To our knowledge, the control of substrate specificity by changing the buffer system has not yet been reported for catalysis of solvolysis reactions of p -nitrophenyl esters.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The 4-(dialkylamino)pyridine-functionalized polymers have been widely regarded as useful model systems for attaining goals of mimicking enzymic efficiency and selectivity. Macromolecule 1 containing the 4-(dialkylamino)pyridine functionality and a bis(trimethylene)disiloxane group in its backbone structure exhibits enzyme-like substrate specificity in the solvolysis of 2 ( n = 2−18) . Recently, we have found that specific salting-in effects of tris(hydroxymethyl)methylammonium ion lead to 1 -catalyzed hydrolysis reaction of 2 ( n = 2−16) with clear preference for 2 ( n = 6) in aqueous solution, , which is the same substrate specificity obtained with cholesterol esterase , in the hydrolysis of p -nitrophenyl esters 2 . The salting-out effects of sodium chloride were found to reduce significantly the substrate preference for 1 -catalyzed solvolysis of 2 ( n = 10−16) at higher NaCl concentrations .…”
Section: Introductionmentioning
confidence: 99%